Penafsiran Hamka tentang Ayat Kemajemukan dalam Tafsir Al-Azhar - Muwaffaq, Moh Mufid (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2019)
Plurality is often deemed as something natural that may become a basis for unity. In Indonesia, Muslims’ thought on the issue has played an instrumental role in organizing the plurality. This article displays the stance of Buya Hamka, one of the most important figures of modernist camp of Muslims in the early stage after Indonesia’s independency, on the issue of plurality by delving into Hamka’s Tafsir al-Azhar. Hamka points out that a Muslim ought to focus on whatsoever lessons they got from others, rather than differences that may trigger social conflict. Yet when it comes to religious plurality, Hamka shows a sort of harsh stance particularly against the Christians. He mentions some aspects he considers theologically incorrect. In doing so, Hamka alludes to many social contexts he lives in, including the practice of endogamy conducted by Arab community on which he criticizes quite loud. The very character echoes the argument of scholars studying tafsirs circulating in Indonesia.